Multimorbidity and Polypharmacy in Chinese Emergency Department Patients With Atrial Fibrillation and Impacts on Clinical Outcomes - Wang, Juan; Yang, Yan-min; Zhu, Jun; Zhang, Han; Shao, Xing-hui (Frontiers in Cardiovascular Medicine, 2022)
Background and Objects: Few studies focus on multimorbidity and polypharmacy in Chinese atrial fibrillation (AF) patients. We examined the impact of multimorbidity, polypharmacy, and treatment strategies on outcomes in Chinese emergency department (ED)AF patients. We also assessed factors associated with vitamin K antagonist (VKA) non-use in AF patients with multimorbidity or polypharmacy. Methods: 2015 AF patients who presented to emergency department (ED) were enrolled from Nov 2008 to Oct 2011, mean follow-up of 12-months. Cox regressions were performed to identify the impact of multimorbidity and polypharmacy on clinical outcomes. Results: 665 patients in low morbidity group (≤1 comorbidity), 608 patients in moderate morbidity group (2 comorbidities), 742 patients in high morbidity group(≥3 comorbidities). 570 patients (28.3%) had polypharmacy (≥5 medications). High and moderate morbidity groups were significantly associated with a higher risk of all-cause death (HR 2.083, 95%CI 1.482-2.929; HR 1.713, 95%CI 1.198-2.449), CV death (HR 2.457, 95%CI 1.526-3.954; HR 1.974, 95%CI 1.206-3.232) and major bleeding (HR 4.126, 95%CI 1.022-16.664; HR 6.142, 95%CI 1.6789-22.369) compared with low morbidity group. In VKA subgroup, only high morbidity group was associated with a higher risk of all-cause death (HR 2.521, 95%CI 1.482-2.929), but not significantly in other events. For polypharmacy category, there were no significant statistics among these endpoints. Coronary artery disease (CAD), hypertension, chronic obstructive pulmonary disease, and antiplatelet therapy were independent predictors for VKA non-use in whole cohort, and patients with multimorbidity. CAD and antiplatelet therapy were independent predictors for VKA non-use in patients with polypharmacy. Conclusion: Multimorbidity was associated with worse outcomes in Chinese ED AF patients. Polypharmacy showed no significant statistics among these outcomes. CAD and antiplatelet therapy were independent predictors of VKA non-use in patients with multimorbidity or polypharmacy.